Development of a Web-Based E-UKGM Application to Improve the Performance of Oral Health Cadres (A Study in the Padangsari Community Health Center Service Area, Semarang City) - Moch Raja Haffidz; Diyah Fatmasari; Bambang Sutomo (International Journal of Innovative Science and Research Technology, 2026)
Background: The implementation of the Community Dental Health (UKGM) continues to face challenges in recording, reporting, and monitoring activities, which are predominantly conducted manually, resulting in suboptimal program implementation. In addition, the utilization of digital technology to support UKGM implementation by community dental health cadres remains limited. These conditions prompted the development of the E-UKGM web-based application as a supporting tool for implementing UKGM activities. Objective: To develop the E-UKGM web-based application and to analyze its feasibility and effectiveness in improving the performance of community dental health cadres in implementing UKGM activities. This study employed a Research and Development (R&D) approach using a modified Borg and Gall model, with system development based on the Waterfall method. The effectiveness of the application was evaluated using a pre-experimental design with a one-group pretest-posttest design. The study involved 30 community dental health cadres selected through total sampling. Feasibility was assessed through expert validation using Aiken's V and the Intraclass Correlation Coefficient (ICC), while effectiveness was analyzed using the Wilcoxon Signed-Rank Test.